Two new species of the fallax-pezizoides complex in Helvella (Helvellaceae, Pezizales) from Yunnan, China - Bao, Shu-Xin; Li, Ying; Zhou, De-Qun; Thongklang, Naritsada; Yu, Feng-Ming; Zhao, Qi (Phytotaxa, 2023)
During the investigation of Helvella in Yunnan, China, four saddle-like specimens were collected and studied. Through a comprehensive analysis of both morphological traits and phylogenetic data from LSU and hsp90 sequences, the four collections were identified and are described as two new species, i.e., Helvella liquii and H. pseudoatra. Helvella liquii stands out with its distinctive features, including the fusion of the pileus margin with the stipe, a slightly rugose coffee blackish surface on the receptacle, and relatively broad apex of the paraphyses. Helvella pseudoatra is characterized by a pubescent receptacle surface that exhibits shaded or dark grey to greyish brown. Additionally, the upwardly white to brown stipe with a basally white to greyish color further distinguishes this species. To provide a comprehensive understanding of these newly discovered taxa, detailed descriptions and illustrations of both Helvella liquii and H. pseudoatra species are accurately documented.